Resveratrol Supported on Magnesium DiHydroxide (Resv@MDH) Represents an Oral Formulation of Resveratrol With Better Gastric Absorption and Bioavailability Respect to Pure Resveratrol - Iannitti, Rossana Giulietta; Floridi, Alessandro; Lazzarini, Andrea; Tantucci, Alice; Russo, Roberta; Ragonese, Francesco; Monarca, Lorenzo; Caglioti, Concetta; Spogli, Roberto; Leonardi, Lucio; De Angelis, Massimiliano; Palazzetti, Federico; et al. (Frontiers in Nutrition, 2020)
Resveratrol attracts great interest because of the plethora of in vitro effects at the micromolar concentration range. Unfortunately, these effects are difficult to establish in vivo, due to the low concentration of resveratrol reached. This discrepancy is due to the molecules low solubility in water that favours the propensity for an intestinal absorption rather than in the gastric compartment. To address these challenges, we developed a Solid Dispersion of Resveratrol Supported by Magnesium Di Hydroxide formulation (Resv@MDH). This formulation displays increased water solubility and better bioavailability relative to pure resveratrol in the rabbit animal model. In our study, we evaluated the pharmacokinetics profile of resveratrol in six healthy human subjects following 180 mg of oral resveratrol administration, derived from Resv@MDH or pure resveratrol. Free resveratrol was evaluated in the whole blood sample by using HPLC - MS/MS. In comparison with pure resveratrol that displays an increase of Cmax at about 90 minutes and 2 M, Resv@MDH displays an earlier peak of resveratrol concentration with an increase of Cmax at about 30 minutes and 6 M). The different kinetics suggest a main gastric route for resveratrol absorption from Resv@MDH, where, because of its improved dissolution rate, there seems to be a higher propensity for an acidic environment, as opposed to with pure resveratrol. This conclusion is also supported by the numerical simulation analysis, which considers the principal steps during the oral route administration. Moreover, there is a twofold increase in the amount of free resveratrol with respect to pure resveratrol confirming a better bioavailability observed in the animal model. The characteristic feature of the pharmacokinetic profile of Resv@MDH implies that the beneficial properties of resveratrol in human health should be capitalized on it.